The Impacts of the Dust Radiative Effect on Vegetation Growth in the Sahel. Issue 12 (6th December 2019) - Evans, Stuart; Malyshev, Sergey; Ginoux, Paul; Shevliakova, Elena
Abstract: Many studies have been conducted on the effects of dust on rainfall in the Sahel and generally show that African dust weakens the West African Monsoon, drying the region. This drying is often assumed to produce a positive dust‐precipitation feedback by reducing vegetation cover for the region. We directly test this relationship for the first time by using a model that explicitly simulates vegetation growth and its impact on dust emission. There are several competing effects of dust that affect plant growth: changes to rainfall, downwelling solar radiation, surface temperature, and resultant changes in surface fluxes. Our model finds that the combined effect of these processes decreases vegetation cover and productivity of the Sahel and West Africa. We determine this by comparing experiments with radiatively active dust to experiments with radiatively invisible dust. In modern conditions, the dust radiative effect decreases leaf area by 12%, productivity by 14%, and increases bare soil area by 3% across the Sahel, and by much higher amounts locally. Experiments where the vegetation experiences preindustrial rather than modern CO2 levels show that without stomatal closure, the reductions would be approximately 20–40% stronger. In preindustrial conditions the vegetation response is weaker, despite the dust‐induced rainfall and temperature anomalies being similar. We interpret this as the vegetation being less susceptible to drought in a less evaporative climate. These vegetation responses to dust are evidence of a dust‐vegetation feedback loop whose strength varies with the mean state of the climate and which may grow stronger in the future. Key Points: We present results for the Sahel from a fully coupled general circulation model including both dynamic vegetation and dynamic dust sources Dust radiative effects reduce Sahelian rain, increase the frequency of dry conditions, and reduce vegetation productivity and coverage The strength of the dust effect depends on the mean state of the climate, with vegetation experiencing greater impacts in drier climates